Extremophiles Handbook - Horikoshi, Koki; Antranikian, Garabed; Bull, Alan T.; Robb, Frank T.; Stetter, Karl O. (Springer Japan : Imprint: Springer, 2011)
The Extremophiles Handbook brings together the rapidly growing and often scattered information on microbial life in the whole range of extreme environments. This book will be a useful reference for finding clues to the origin of life and for exploring the biotechnology potential of these fascinating organisms.